2013
DOI: 10.1016/j.commatsci.2012.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stress intensity factors and T-stress to control crack propagation for kerf-less spalling of single crystal silicon foils

Abstract: Monocrystalline silicon (called mono silicon) is extensively used in the electronic and solar photovoltaic industries. During the last decade, many new manufacturing processes have been developed to improve solar cells' efficiency while reducing their cost of production. This paper focuses on a kerf-less technique based on the controlled fracture of silicon foils by depositing an adherent stress-inducing layer on {hkl} cleavage plans. A finite element model (FEM) is defined to study the stress intensity factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Second, we removed the crack-induced damages on the fracture Si surface to minimize the surface recombination of photoexcited carriers and to improve the PEC HER properties. During crack propagation in the spalling process, the area near the crack tips suffers from a significant stress concentration. , This concentrated stress can inevitably induce the formation of defects, which are nano- and microcracks at the fracture surface. , These defects can act as recombination sites and deteriorate the PEC performance by reducing the minority carrier lifetime. To remove the fracture-induced defects, we etched the fracture surface of the 17 μm thick spalled Si using a KOH solution under optimum etching conditions, followed by electroless deposition of the Pt NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we removed the crack-induced damages on the fracture Si surface to minimize the surface recombination of photoexcited carriers and to improve the PEC HER properties. During crack propagation in the spalling process, the area near the crack tips suffers from a significant stress concentration. , This concentrated stress can inevitably induce the formation of defects, which are nano- and microcracks at the fracture surface. , These defects can act as recombination sites and deteriorate the PEC performance by reducing the minority carrier lifetime. To remove the fracture-induced defects, we etched the fracture surface of the 17 μm thick spalled Si using a KOH solution under optimum etching conditions, followed by electroless deposition of the Pt NPs.…”
Section: Resultsmentioning
confidence: 99%
“…During crack propagation in the spalling process, the area near the crack tips suffers from a significant stress concentration. 28,29 This concentrated stress can inevitably induce the formation of defects, which are nano-and microcracks at the fracture surface. 30,31 These defects can act as recombination sites and deteriorate the PEC performance by reducing the minority carrier lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…The same variation was obtained in other investigations on various materials. Bouchard et al [41] have shown that T increases with increasing depth for a mono silicon. In [42], Sherry et al obtained an increase in T in absolute value with the variation of the crack size over the width of a plate.…”
Section: Discussionmentioning
confidence: 96%
“…It is important to note that all parameters of the stressor layers mentioned above have also an impact on the direction of the fracture propagation in the silicon substrate, as reported by several publications [22,[29][30][31].…”
Section: Effect Of the Stressor Layer Materials On The Detachment Of ...mentioning
confidence: 87%